Tinjauan Yuridis Kedudukan Status Tanah di Kawasan Benteng Vastenburg: (Studi Kasus Pada Tanah Bekas Sertifikat HGB Nomor 383 Atas Nama PT Bank Danamon Indonesia) - Hans Blix Baarixur Rahman; Lego Karjoko; Fatma Ulfatun Najicha (Majelis: Jurnal Hukum Indonesia, 2025)
Vastenburg Fort is a cultural heritage area that has been designated by the Department of Culture and Tourism in 2010. In line with this designation, the City Government changed the spatial plan of Surakarta City by revising the Regional Regulation related to the regional spatial plan. In addition, the land status in the Vastenburg Fort area is divided into building use rights granted to the private sector. Even so, the City Government managed to obtain the former HGB land No. 383 which was designated as a Public Service Mall. The change in designation as a Public Service Mall is considered to reflect the need to adjust to the spatial plan in Surakarta City. However, the purpose of spatial planning in the Vastenburg Fort area should be designated for the preservation of cultural heritage. The purpose of this study is to find legal certainty arising from the conversion of former HGB land into a Public Service Mall by the Solo City Government. This study uses an empirical legal studies. The results of this study indicate that the conversion of former HGB land No. 383 in the Vastenburg Fort area by the Surakarta City Government is in accordance with the legislation. As for the City Government, the land is designated for the Public Service Mall in accordance with the spatial plan in Surakarta City in the Surakarta City RTRW Regional Regulation for the preservation of cultural heritage. However, the Surakarta City Government has not yet maximized the acquisition of HGB in the Vastenburg Fort area so that the use of land in the area is more optimal so that it benefits the entire community.